2018
DOI: 10.1017/s0025100318000324
|View full text |Cite
|
Sign up to set email alerts
|

The articulation of /ɹ/ in New Zealand English

Abstract: This paper investigates the articulation of approximant /ɹ/ in New Zealand English (NZE), and tests whether the patterns documented for rhotic varieties of English hold in a non-rhotic dialect. Midsagittal ultrasound data for 62 speakers producing 13 tokens of /ɹ/ in various phonetic environments were categorized according to the taxonomy by Delattre & Freeman (1968), and semi-automatically traced and quantified using the AAA software (Articulate Instruments Ltd. 2012) and a Modified Curvature Index (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Thanks to the relatively less invasive nature of the method and the ease of data collection, sample sizes in ultrasound studies have been typically higher than for EPG, with the median being nine participants (mean 11.8, SD 13). A few recent studies have considerably extended their sample sizes (e.g., 57 speakers in Noiray, Abakarova, Rubertus, Krüger, & Tiede, , 60 in Zharkova, and 62 in Heyne, Wang, Derrick, Dorreen, & Watson, ). As mentioned earlier, ultrasound can be easily used with children and elders ‐ the populations that were previously rather under‐studied given the invasiveness of other articulatory methods.…”
Section: Studying Oral Gestures: a Case Studymentioning
confidence: 99%
“…Thanks to the relatively less invasive nature of the method and the ease of data collection, sample sizes in ultrasound studies have been typically higher than for EPG, with the median being nine participants (mean 11.8, SD 13). A few recent studies have considerably extended their sample sizes (e.g., 57 speakers in Noiray, Abakarova, Rubertus, Krüger, & Tiede, , 60 in Zharkova, and 62 in Heyne, Wang, Derrick, Dorreen, & Watson, ). As mentioned earlier, ultrasound can be easily used with children and elders ‐ the populations that were previously rather under‐studied given the invasiveness of other articulatory methods.…”
Section: Studying Oral Gestures: a Case Studymentioning
confidence: 99%
“…A study of 62 New Zealand English speakers byHeyne et al (2018) found similarly that about 40% produce only tip-down (i.e., bunched) /ɹ/.…”
mentioning
confidence: 98%
“…More frequent retroflexion has also been observed in non-rhotic New Zealand English. In a large-scale ultrasound study of 62 New Zealand English speakers, nearly 20% of subjects produced exclusively retroflex tongue shapes (Heyne et al, 2018). Like Mielke et al (2016), Heyne et al (2018) also considered the equivalent of our Front Up classification to be bunched and not retroflex.…”
Section: Articulation Of Anglo-english /R/mentioning
confidence: 92%
“…In a large-scale ultrasound study of 62 New Zealand English speakers, nearly 20% of subjects produced exclusively retroflex tongue shapes (Heyne et al, 2018). Like Mielke et al (2016), Heyne et al (2018) also considered the equivalent of our Front Up classification to be bunched and not retroflex. If we do the same, the percentage of exclusively retroflex users in Anglo-English (25%) and New Zealand English (nearly 20%) are remarkably consistent.…”
Section: Articulation Of Anglo-english /R/mentioning
confidence: 92%
See 1 more Smart Citation